Virtue Is Its Own Reward: Kant on Moral Contentment - Kolomy, Vojtech (Con-Textos Kantianos. International Journal of Philosophy, 2025)
In the last few decades, Kantian scholars have increasingly drawn attention to the fact that, for Kant, virtuous persons do not do their duty with disgust, but rather that they experience a special moral contentment (moralische Zufriedenheit). However, Kant does not seem to have been very interested in this moral contentment, so what we find are rather allusions, often difficult to reconcile, than an elaborated account of moral contentment. This article offers a systematic reconstruction of the concept. Through close analysis of Kant’s Critique of Practical Reason and related writings, I show that moral contentment is neither a pathological nor properly moral feeling (the feeling of respect), nor can it be reduced to the absence of reproaches of moral conscience. Rather, it is a uniquely moral kind of “negative satisfaction”: an indirect enjoyment of inner freedom, made possible through independence from inclination, and it appears as directly connected to Kant’s specific conception of virtue understood as one’s moral strength in fulfilling one’s duty.